Strategic term rewriting and its application to a VDM-SL to SQL conversion - Alves, Tiago Miguel Laureano (2005)
We constructed a tool, called VooDooM, which converts datatypes in Vdm-sl into Sql relational data models. The conversion involves transformation of algebraic types to maps and products, and pointer introduction. The conversion is specified as a theory of refinement by calculation. The implementation technology is strategic term rewriting in Haskell, as supported by the Strafunski bundle. Due to these choices of theory and technology, the road from theory to practise is straightforward.